Inactivation of harmful algae using photocatalysts: Mechanisms and performance. (20th March 2021) - He, Xinghou; Wu, Pian; Wang, Shanlin; Wang, Anzhi; Wang, Chunlei; Ding, Ping
Abstract: The blooms of harmful algae in waterbodies have become increasing events in the world owing to the serious eutrophication spreads and extreme climate, posing adversely affected human and ecosystems health. Photocatalysis is seen as one of the most effective methods for harmful algae inactivation. In recent decades, many studies in the view of rudimentary knowledge, basic mechanism and modification technique of photocatalytic materials in deactivating algae have been reported. The primary objective of the present article was to provide a systematic overview on recent research progresses, toward application of semiconductor photocatalysts for the destruction of algal species. The proposed damage mechanisms of photocatalysts for inhibiting algal growth including oxidative stress and physical restraints were summarized. On the basis of numeric metrics such as quantum yields (QY), space time yields (SY), and figures of merit (FOM), the photocatalytic performance of various photocatalysts was particularly evaluated in terms of chlorophyll-a and cyanobacteria removal. In the view of chlorophyll-a degradation, Ag/AgCl@ZIF-8 coated sponge exhibited the best performance with QY, SY, and FOM values of 8.09E-09 molecules/photon, 8.09E-06 molecules/(g·photon), and 4.73E-13 mol L/(g·J·h), respectively. In the view of algal cells inactivation, the best performance was seen in F–Ce–TiO2/expanded perlite composite (F–Ce–TiO2 /EP450) with high adjusted QY (7.74E-17 cells/photon), SY (1.94E-17 cells/(g·photon)), and FOM values (4.54 cell·L/(g·J·h)). Finally, a brief summary about current knowledge gaps, probable opportunities and future research priorities in the emergent field of further development of photocatalytic composite for algal blooms control were discussed. We believe this review will be helpful to enhance our insight of the damage mechanisms responsible for the inactivation of algae with photocatalysts. Graphical abstract: Image 1 Highlights: The research of photocatalysts for harmful algae inactivation was reviewed. Proposed mechanisms regarding the damage of algal cell were presented. Focuses on performance of various photocatalysts were assessed. Future research needs for algal bloom control were suggested.